Respuesta :
[tex] {81p}^{2} - 144pq + {64q}^{2} \\ (9p - 8q)(9p - 8q) \\ = {(9p - 8q)}^{2} [/tex]
hope this helps you!
The factor of the given equation is [tex](9p - 8q)^2[/tex].
Given that,
- The equation is [tex]81p^2 -144pq + 64q ^2[/tex].
- Here we need to factor it.
Based on the above information, the calculation is as follows:
[tex]= 81p^2 -144pq + 64q ^2\\\\= (9p - 8q) (9p - 8q)\\\\= (9p - 8q)^2[/tex]
Therefore we can conclude that The factor of the given equation is [tex](9p - 8q)^2[/tex].
Learn more: brainly.com/question/6201432